Risk Assessment of Mobile and Non-Mobile Steel Scaffolding Installation : A Warehouse Construction Project Case Study - เกตุทิพย์ ภิมพ์ปวีณ์; สอนวงษ์ พิพัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aims to analyze and assess the risks associated with the installation of fixed and mobile steel scaffolding structures with heights ranging from 2 to 10 meters in a warehouse construction project. The research applies the Job Safety Analysis (JSA) in conjunction with Fault Tree Analysis (FTA) techniques, following the guidelines set forth by the Ministry of Industry Regulation B.E. 2543 concerning hazard identification, risk assessment, and the development of risk management plans. The study was conducted with the collaboration of 20 construction professionals with over five years of experience, including project managers, engineers, safety officers, foremen, and scaffolding installation workers. The findings revealed that both types of scaffolding shared eight installation steps, differing only in one: fixed scaffolding required ground preparation, while mobile scaffolding was limited to installation on concrete surfaces. JSA identified four high-risk events in fixed scaffolding: uneven ground, uneven base adjustment, use of damaged equipment, and failure to wear fall protection equipment. The latter three were also observed in mobile scaffolding. FTA indicated that the primary risks—scaffolding collapse and falls from height—stemmed from 13 contributing events, with no statistically significant difference (p > 0.05) between the two scaffold types. Additionally, the failure to use fall protection equipment was associated with 15 contributing factors, also without a statistically significant difference. Based on the results, risk control and mitigation measures were proposed using the 4M1E framework, focusing on: safety training and enforcement for personnel (Man); inspection and certification of scaffolding equipment to ensure usability (Machine/Material); establishment of systematic control procedures (Method); and ensuring stable, safe worksite conditions prior to installation (Environment).